FEATURES OF CIRCADIAN RHYTHM DISORDERS OF RESPIRATORY RATE IN ACUTE RENAL INJURY IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Even the most modern respiratory support devices are not able to adequately compensate for the functional fluctuations of the respiratory system in conditions of severe infectious and inflammatory stress and in the absence of renal detoxification function in children with acute renal injury (AKI). Violations of the circadian rhythm of respiratory rate (BH) in this group of patients are a poorly studied but clinically significant phenomenon.
Keywords: acute renal injury; circadian rhythm; respiratory rate; children; peritoneal dialysis; hemodialysis; respiratory support; multiple organ failure; intensive care; age characteristics